Criminal Law Protection for Domestic Workers Victims of Domestic Violence by Employers - Prisko Yanuarius Djawaria Pare; Anna M. W. Ndapa; Karolna S. Wea; Natalia E. Leka; Rosalina Wea (Indonesian Journal of Advanced Research, 2024)
This article discusses the importance of criminal law protection for domestic workers who are victims of domestic violence by their employers. Domestic violence against domestic workers is a serious problem and should not be ignored. Through criminal law analysis, this article identifies the challenges and obstacles faced by domestic workers who are victims of violence in obtaining justice. In this article, we highlight the need for a revision of the criminal law that is more stringent in providing protection for domestic workers who are victims of violence. We also discussed the importance of increasing public awareness and education as well as the government's role in protecting the rights of domestic workers.